Kajian Pustaka Montelukas: Pengobatan Asma pada Anak - Selinda Anggia Devi; Fauna Herawati Herawati (Malahayati Nursing Journal, 2023)
ABSTRACT Chronic airway inflammation is a major characteristic of asthma. Montelukast is a class of leukotriene receptor antagonists (LTRA) which has the most widely used anti-inflammatory properties because it shows the best effectiveness and safety. Many in vitro and in vivo experimental clinical studies have been published in the last 10 years covering the effectiveness and safety of montelukast in childhood asthma of varying degrees of severity. Montelukast is used as an alternative monotherapy for the ICS class or as an adjunct to enhance the anti-inflammatory and sparing effects of corticosteroids. montelukast as a treatment for asthma in children can be given in cases of mild to moderate persistent asthma, wheezing due to viruses, asthma due to exercise, and intolerance of steroid use in children. The advantages of montelukast as monotherapy are fast onset in controlling asthma, low side effects, given once daily oral administration without the need for an inhaler thereby increasing pediatric patient compliance.           Keyword: Asthma, Children, Montelukast, Cysteinyl Leukotriene Receptor Antagonist.  ABSTRAK Inflamasi saluran napas kronis merupakan karakteristik utama asma. Montelukas merupakan golongan antagonis reseptor leukotrien (LTRA) memiliki sifat antiinflamasi yang paling banyak digunakan karena menunjukkan efektivitas dan keamanan terbaik. Penelitian klinis eksperimental baik in vitro maupun in vivo sudah banyak diterbitkan dalam 10 tahun terakhir mencakup efektivitas dan keamanan montelukas pada asma anak dengan derajat keparahan berbeda-beda. Montelukas digunakan sebagai monoterapi alternatif untuk golongan ICS atau sebagai tambahan untuk meningkatkan efek antiinflamasi dan meminimalisir penggunaan kortikosteroid. Montelukas sebagai pengobatan asma pada anak dapat diberikan pada kasus asma ringan sampai dengan persisten sedang, sesak oleh karena virus, dan asma akibat aktivitas berat, serta kondisi intoleransi steroid. Keuntungan montelukas sebagai monoterapi antara lain memiliki waktu onset cepat dalam mengendalikan asma dengan efek samping rendah pada pemberian oral sehari sekali tanpa penggunaan inhaler sehingga meningkatkan kepatuhan pasien anak. Kata Kunci: Asma, Anak, Montelukas, Cysteinyl Leukotriene Receptor Antagonist.